Analisa Sebaran Kebisingan Akibat Aktivitas Landing Dan Take-Off Sekitar Bandar Udara Sultan Aji Muhammad Sulaiman Balikpapan - Alamsyah, Alamsyah (Kurva S : Jurnal Keilmuan dan Aplikasi Teknik Sipil, 2023)
Noise is defined as unwanted sounds that disturb hearing and can reduce the hearing ability of exposed individuals. Therefore, information on noise levels is needed to determine the noise distribution at Sultan Aji Muhammad Sulaiman Airport in Balikpapan. The noise contours in this study were based on flight data over five days. According to the study, the total noise-affected area at Sultan Aji Muhammad Sulaiman Airport is 0.039 km², with residential areas located 2 km from the runway. Planting noise-dampening trees around residential houses can help reduce noise levels.From the evaluation and data analysis, information such as flight schedules and airport noise data were obtained. Based on the WECPNL noise analysis calculation, the noise level at the airport (apron area) was found to have an impact on employees that remains within acceptable threshold limits at 73.18 dB. However, the noise level in residential areas showed a significant impact on the community, reaching 91.26 dB.